Analisis Pengaruh Lingkungan Kerja dan Gaya Kepemimpinan Terhadap Kinerja Pegawai dengan Motivasi Kerja sebagai Variabel Intervening - Jhon Sepron Defretus Liem (Fakultas Ekonomi Universitas Islam 45, 2025)
This study aimedat determining the significance of the influence of the work environment and leadership style on work motivation and performance of the employees of the Department of Population and Civil Registration (DISDUKCAPIL) of Kupang city.The population were 75 employees and they were utilised as the sample of this study.Techniques and tools of data collection were questionnaires and documentation.Data analysis techniques was in the form of descriptive statistical analysis using the Levis formula and inferential statistical analysis through the SEM-PLS approach with the help of SmartPLS software.Value of the t-statistic was used to prove the hypothesis.The results showed that the variables of the work environment and leadership style had a direct effect on work motivation and performance of DISDUKCAPIL employees in Kupang city. However, the variables of work environment and leadership style had no effect on the performance of DISDUKCAPIL employees in Kupang City through employees’ motivation